The Pragmatic Approach to Heritage from the Perspective of Taha Abderrahmane - djaalab, asmaa; abdessalam, yassmina (El Omda in Linguistics and Discourse Analysis, 2022)
This research paper attempts to identify how Taha Abd al-Rahman has invested in the mechanisms of approximation of science transferred from the Greek field to the field of Islamic deliberation. It will shed light on one model of approximation, which is the linguistic approximation of logic according to Ibn Hazm, in order to reveal the mechanisms that make it conform to the requirement of the Arabic linguistic structure, preserving the peculiarities of the field of Islamic deliberation.